Hubungan Partisipasi Pendengar dalam Event Off-Air dan Partisipasi Interaksi Pendengar melalui Social Media Online dengan Frekuensi Mendengarkan Radio 105,2 SSFM - Annisa Kusumawardhani; Tandiyo Pradekso; Djoko Setyabudi; Nurrist Surayya Ulfa (Interaksi Online, 2014)
Based on AC Nielsen data, the scale cume obtained by the Radio 105.2 SSFM decreased by 2,000 listeners in October to December of 2012. It shows that the activity of a vigorous campaign conducted by the Radio 105.2 SSFM through event off-air and online social media, inversely proportional to the AC Nielsen research data results, which demonstrate the scale cume of the SSFM 105.2 radio decreased. Thus, this study aimed to finding out the correlation among audience’s participation in off-air event (X1), audience’s participation in interaction through online social media (X2), and audience's frequency of listening on the Radio 105,2 SSFM (Y).Theoretical framework are used as a basic premise in this study is the theory of classical conditioning by Ivan Pavlov and Expectancy Value Theory, and social information processing theory by Walter. Classical conditioning theory and Expectancy Value Theory helps to explain that the association established between off-air event with the radio 105.2 SSFM, can motivate audience to act towards the radio 105.2 SSFM. While the social information processing theory helps to explain that the activity of the interaction between the audience with the radio 105.2 SSFM in cyberspace, is pioneering the future of relationship commitment, namely to increase the loyalty of listeners to the radio 105.2 SSFM. The method used on this research is quantitative-survey, involving 100 respondents and non-randomly selected using accidental sampling technique. The hypothesis testing tool used is a statistical test of correlation coefficient kendall's tau-b, with the help of SPSS ver. 16 for Windows.The results of this study are : (1) there is no correlation between participation in audience’s participation in off-air event and audience's frequency of listening on the Radio 105,2 SSFM, and (2) there is a significant correlation between audience’s participation in interaction through online social media and audience's frequency of listening on the Radio 105,2 SSFM. Thus the recommendations given to the radio 105.2 SSFM which can increases the frequency of the listening on the radio 105,2 SSFM by the audience are : (1) the need to review of the use of off-air events as a tool of brand activation by the radio 105.2 SSFM, and (2) the need of a massive effort to use social media online as a tool of brand activation by the radio 105.2 SSFM.Keyword : Off-Air Event, Online Social Media, Frequency of Listening the Radio